Improving the performance of edible food packaging films by using nanocellulose as an additive - Zhang, Wanli; Zhang, Yiqin; Cao, Jiankang; Jiang, Weibo (International journal of biological macromolecules, 2021)
Due to the environmental pollution problems caused by plastic-based packaging, the development of edible food packaging films is imminent. However, the performance of most edible packaging films is insufficient to meet practical applications, so recent studies have focused on the research of various fillers to improve film properties. This article reviews recent applications of cellulose nanocrystals (CNC) and cellulose nanofiber (CNF) in edible food packaging films including the effect on thickness, optical properties, barrier properties, water sensitivity, mechanical properties, antioxidant and antimicrobial properties. The main conclusion of this review is that the incorporation of CNC and CNF could significantly improve the performance of edible food packaging films. Particular finding is that although CNC and CNF can be used as excellent addition to improve the performance of edible food packaging films, there is a key “optimum” concentration. In addition, we also found that CNC and CNF as excellent controlled release agents and stabilizers significantly increased the antioxidant and antibacterial properties of edible food packaging films. [Display omitted] •Recent developments of nanocellulose incorporated edible food packaging (EFP) films.•Nanocellulose is excellent enhancer in EFP films.•There exist an “optimum” concentration of added nanocellulose in EFP film.•Nanocellulose crystals are more functionally stable than nanocellulose fibers.•Nanocellulose is excellent controlled release agent and stabilizer in EFP films.